Respuesta :

Answer:

Step-by-step explanation:

if 2x^2 = 8x - 3

Move terms to the left side

2x^{2}=8x-3

2x^{2} - (8x - 3)= 0

Distribute

2x^{2}-8x+3=0

Use quadratic formula

x=8± √-8^2-4*2*

           2*2

Simplify

x=8± 2√ 10

           4

Separate the equations

x=4- √ 10

           2

x=4+ √ 10

           2

Solve

     x=4-3.2      = 0.4

           2

     x= 4+3.2       = 3.6

           2

let me know if I'm wrong I did this mentally and i think i might have messed up somewhere but I'm like 90% this is correct

ACCESS MORE